2011
DOI: 10.3928/1081597x-20110210-02
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive Keratectomy After Late Traumatic LASIK Flap Loss

Abstract: Treating a patient with traumatic LASIK flap loss can be done by careful, conservative treatment of the abrasion followed by correction of the refractive error using PRK with MMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…On the other hand, total avulsion of the LASIK corneal flap (sometimes with flap loss) is much less common. This event has been related with intraoperative free caps but also has been reported in English literature in five cases of hinged flaps up to four years after initial surgery 3, 4, 5, 6, 7, 8, 9. According to our knowledge, this is the first report of traumatic loss of a LASIK flap occurring so late (13 years) postoperatively.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…On the other hand, total avulsion of the LASIK corneal flap (sometimes with flap loss) is much less common. This event has been related with intraoperative free caps but also has been reported in English literature in five cases of hinged flaps up to four years after initial surgery 3, 4, 5, 6, 7, 8, 9. According to our knowledge, this is the first report of traumatic loss of a LASIK flap occurring so late (13 years) postoperatively.…”
Section: Introductionsupporting
confidence: 61%
“…Searching the MEDLINE literature database through PubMed interface we found that only 12 cases have been reported in the English literature (Table 1). 3, 4, 5, 6, 7, 8, 9…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations